Protoplanetary disc evolution affected by star-disc interactions in young stellar clusters - Rosotti, Giovanni Pietro; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2014)
Abstract. Most stars form in a clustered environment. Therefore, it is important to assess how this environment influences the evolution of protoplanetary disc